2020
DOI: 10.1371/journal.pone.0240621
|View full text |Cite
|
Sign up to set email alerts
|

Programmatic evaluation of feasibility and efficiency of at birth and 6-week, point of care HIV testing in Kenyan infant

Abstract: Background Testing infants at birth and with more efficient point of care (POC) HIV diagnostic can streamline EID and expedite infant ART initiation. We evaluated the implementation of at birth and 6-week POC testing to assess the effectiveness and feasibility when implemented by existing hospital staff in Kenya. Methods Four government hospitals were randomly assigned to receive a GeneXpert HIV-1 Qual (n = 2) or Alere m-PIMA (n = 2) machine for POC testing. All HIV-exposed infants enrolled were eligible to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
(58 reference statements)
1
18
0
Order By: Relevance
“…Adaptions to implementation that occurred throughout the study period (modified logistics in terms of machine location, implementing personnel, workflow, and patient flow; improved mechanisms of interdepartmental communication; continuous OTJ training and site supervision) helped mitigate some of these challenges, but issues like power blackouts, machine breakdown, and high cost of cartridges will remain persistent barriers to sustainable implementation. These qualitative results support the quantitative evidence from our parent study [ 10 , 19 ] that suggests that POC testing can expedite infant diagnosis, but challenges in POC implementation can result in missed opportunities for testing [ 10 ] and delayed ART initiation [ 19 ]. Providers felt that engagement beyond the implementing team was insufficient and discussed how more active engagement from stakeholders in the inner and outer settings was needed to continue implementation post-study.…”
Section: Discussionsupporting
confidence: 79%
“…Adaptions to implementation that occurred throughout the study period (modified logistics in terms of machine location, implementing personnel, workflow, and patient flow; improved mechanisms of interdepartmental communication; continuous OTJ training and site supervision) helped mitigate some of these challenges, but issues like power blackouts, machine breakdown, and high cost of cartridges will remain persistent barriers to sustainable implementation. These qualitative results support the quantitative evidence from our parent study [ 10 , 19 ] that suggests that POC testing can expedite infant diagnosis, but challenges in POC implementation can result in missed opportunities for testing [ 10 ] and delayed ART initiation [ 19 ]. Providers felt that engagement beyond the implementing team was insufficient and discussed how more active engagement from stakeholders in the inner and outer settings was needed to continue implementation post-study.…”
Section: Discussionsupporting
confidence: 79%
“…In our parallel pilot study of PoC testing at these same sites, we experienced higher rates of missed testing opportunities due to machine/stock outs or invalid results (23.3%), 29 and delays in ART initiation still occurred largely due to the initial novelty of PoC in this setting. 29 , 30 Other larger PoC studies have reported more favorable findings, 19 , 31 and the benefit of PoC may be greater in settings with longer delays for laboratory-based PCR results. Furthermore, PCR HIV testing at birth and 6-week has been assessed as cost-effective, compared with EID at 6 weeks alone.…”
Section: Discussionmentioning
confidence: 97%
“…We estimated the following PCR monitoring-related costs in year 1: (1) GeneXpert ® instruments, (2) uninterrupted power supplies (UPS), (3) warranties, (4) calibration kits, (5) test cartridges, and (6) shipping for instruments and test cartridges. During years two to ve, the following PCR monitoringrelated costs were included: (1) calibration kits, (2) test cartridges, and (3) shipping costs for cartridges.…”
Section: Costsmentioning
confidence: 99%
“…The system is widely used in low-and middle-income countries (LMICs) for infectious diseases (e.g., TB, HIV) and utilization is increasing in a handful of oncology applications including BCR-ABL1 [5,6]. The Cepheid platform has many desired features in the LMIC setting, including ease and e ciency of use (less technical training needed, with exible use between batches or single assays), easy shipping solutions (cartridges rather than many different reagent supplies), high reproducibility, and reliable precision and accuracy.…”
Section: Introductionmentioning
confidence: 99%